Grammatographisches Wissen bei deutschen Muttersprachlern und türkischen Deutschlernern - Weingarten, Rüdiger (My University, 2016)
The cognitive prerequisites for the German writing system is comprised of two parts. Firstly, there is a rule-based mechanism that specifies how to transfer phonological word forms into graphemic forms. Secondly, there is an orthographic lexicon that contains graphemic word forms, especially for those words which are not written in accordance with the rule-based mechanism. In this article, a study is presented which aims at the mastering of the rule-based mechanism of German L1-writers and Turkish L2-writers of German, with the Turkish group being differentiated into two levels of proficiency. The participants of this study were asked to write sentences with pseudowords. As an outcome we expect insights into the acquisition of the German writing system by foreign language learners. Specifically, we will demonstrate that the grammatographic aspects of the German writing system can be mastered at least at an intermediate level of proficiency.
Keywords: German; Turkish; writing system; cognitive system; grammatography; second language writing acquisition